Analysis study of quality factor and bit error rate at wavelength change - Fadhela Thaeer Mahmood; Alaa H. Ali; Alaa H. Ali Haeder (Institute of Advanced Engineering and Science, 2022)
Gigabit - per - second data speeds can be achieved via free space optics (FSO) lines, which needless system complexity. On the other hand, the link's availability across a wide range of atmospheric circumstances is a major worry. As a result of the increased signal attenuation caused by the linkages being weather - dependent, their efficiency decreases. Up to 70 dB/km of attenuation can be caused by bad weather on a 500 - meter free space optics link. In this work, transmission windows of 1310 nm, 850 nm , and 1550 nm are analyzed and compared using the free space optics link. by using the Simulation program o pti system such as the q uality factor, the minimal bit error rate (BER), and the e ye diagram is taken into account. Analyzer findings are compared to establish the optimal wavelength for a transmitter under poor weather conditions.